Sistem Informasi Pelayanan Jasa Cuci Kendaraan Bermotor Berbasis Web - Endah Wiji Lestari; Fitria Ramdani (Universitas Insan Pembangunan Indonesia, 2020)
Abstract: Every year the number of motor vehicles in Indonesia, especially in the capital city of Jakarta, is always increasing, based on data from the DKI Jakarta BPS in 2016 the number of motor vehicles has grown by an average of 5% over the past 5 years. More and more motor ve-hicles make more air pollution, besides not good for health, pollution also makes motor vehicles dirty quickly, but behind all of that, pollution provides greater business opportunities in the field of motor vehicle washing services. In this study, the authors made observations on several a mo-tor vehicle washing service especially in the Cipinang area. In some of the places we visited to carry out these observations, most of the business services still use conventional systems to this day. For example, in the recording of transactions for each motorized vehicle that is washed, they record it in paper media which will later be collected to be included in the daily transaction in a ledger. Then for each transaction that occurs in one month that will be reported to the busi-ness service owner, the cashier recap every day for one month to be shown to the owner later using the ledger. In the development era that has been very sophisticated with the presence of new technology at this time of course it has been very lagging behind for the current system of business services, therefore the author wants to make a computerized system such as the appli-cation of point of sale cashiers which will hopefully be able to facilitate cashiers who tasked with these business services to input transactions that occur and make reports and calculate fi-nancial statements. This system uses system development with the waterfall method where the stages start from system design, system design, writing program code, system testing to system maintenance.Keywords: Information System; Service; Waterfall